Tinjauan Kriminologis Terhadap Kejahatan Prostitusi Online Melalui Aplikasi MiChat di Wilayah Hukum Kota Jambi - Khoirunnisya, Khoirunnisya; Liyus, Herry (Faculty of Law, Universitas Jambi, 2024)
The purpose of this study was to find out the factors that led to online prostitution crimes through the MiChat application and what efforts were made by the Police in dealing with online prostitution crimes through the MiChat application. The formulation of the research problem is in the form of what are the factors that cause online prostitution crimes through the MiChat application and what are the countermeasures carried out by the Police in dealing with online prostitution crimes through the MiChat application. The type of research used is empirical juridical research, namely research that uses facts that occur in the field obtained from observations and interviews. The results of this study are that the factors that cause online prostitution crimes through the MiChat application in the jurisdiction of Jambi City are economic factors, technological progress factors, environmental factors, educational factors and lifestyle factors. The results of the research regarding the countermeasures carried out by the Police in overcoming online prostitution crimes through the MiChat application in the jurisdiction of Jambi City, namely using two types of efforts in the form of preventive efforts and revressive efforts.